Emotion recognition based on multi-modal physiological signals and transfer learning - Fu, Zhongzheng; Zhang, Boning; He, Xinrun; Li, Yixuan; Wang, Haoyuan; Huang, Jian (Frontiers in Neuroscience, 2022)
In emotion recognition based on physiological signals, collecting enough labeled data of a single subject for training is time-consuming and expensive. The physiological signals' individual differences and the inherent noise will significantly affect emotion recognition accuracy. To overcome the difference in subject physiological signals, we propose a joint probability domain adaptation with the bi-projection matrix algorithm (JPDA-BPM). The bi-projection matrix method fully considers the source and target domain's different feature distributions. It can better project the source and target domains into the feature space, thereby increasing the algorithm's performance. We propose a substructure-based joint probability domain adaptation algorithm (SSJPDA) to overcome physiological signals' noise effect. This method can avoid the shortcomings that the domain level matching is too rough and the sample level matching is susceptible to noise. In order to verify the effectiveness of the proposed transfer learning algorithm in emotion recognition based on physiological signals, we verified it on the database for emotion analysis using physiological signals (DEAP dataset). The experimental results show that the average recognition accuracy of the proposed SSJPDA-BPM algorithm in the multimodal fusion physiological data from the DEAP dataset is 63.6% and 64.4% in valence and arousal respectively. Compared with joint probability domain adaptation (JPDA), the performance of valence and arousal recognition accuracy increased by 17.6% and 13.4% respectively.